Effect of connectivity and terminal functionality on mesophase behaviour of thermotropic liquid crystals containing biphenyl units - Ranganathan, T.; Ramesh, C.; Kumar, Anil (Liquid Crystals, 2005)
A series of 4,4'-disubstituted biphenyls, designated as series HBC, in which, one substituent is an ester group linked directly to the ring and the other is the hydroxy-containing group O(CH2)(n)OH, have been prepared and analysed by differential scanning Calorimetry, polarizing optical microscopy and X-ray diffraction. The introduction of a trimethylene unit between the ester functional group and the biphenyl moiety of the HBC series gives rise to the HBB series, which did not exhibit liquid crystalline behaviour. Interestingly, mesophase behaviour could be restored by replacing the methylene group ( of the trimethylene unit) that was directly attached to the biphenyl ring by a keto group (HBOB series). When the terminal hydroxy group of these three series was substituted by a group such as acetoxy or hydrogen, the transition temperatures were reduced, and the disappearance of mesophase behaviour was observed in some cases. However, this could be recovered by the replacement of the ester group by a carboxylic acid group.